Projectile weapons before the bow: metric data from the southern Andes - Marsh, Erik Johnson (2021)
Projectile technology was a significant factor in the demographic expansion of Homo sapiens out of Africa. Settlement in the Americas was made possible by a series of human strategies including the use of atlatls and throwing spears. These were the dominant weapons for much of the continent’s human history, prior to the initial appearance of the bow and arrow. This significant technological breakthrough was culturally transmitted over a wide region and accompanied major economic changes. Most methods for distinguishing archaeological dart and arrow projectile points rely on metric comparisons to ethnographic collections (Shott 1997) and the general trend that spear points are large and heavy, atlatl dart points are somewhat smaller, and arrow points are the smallest. In the southern Andes, lithic points prior to the use of the bow include fishtail points (late Pleistocene–early Holocene), large stemmed and lancolate points (early Holocene) and triangular points (middle–late Holocene). This paper’s goal is to begin to characterize the metric variability of projectile points prior to the introduction of the bow in the southern Andes. To do this, we selected points from contexts that are unambiguously prior to the bow, based on associations with 1) preserved wood atlatl elements or 2) radiocarbon dates that are well prior to the introduction of the bow. We present data for 64 lithic points from the site Los Morrillos (30°S) in levels dated 4000–7500 years BP and at nine other sites (32–34°S) from levels dated 2000–7500 years BP. These points have also been analyzed morphologically to reduce noise by excluding points reused as knives. These data will allow us to estimate the metric range of pre-bow projectile points from secure archaeological contexts (Castro et al. 2021). This will help provide a stronger comparative baseline for identifying arrow points, which is currently done with ethnographic measurement that sometimes di!er significantly from archaeological ones. This will also help establish a comparative baseline for the Andes, where regional variation may also be a factor in variable point sizes.